Aerobic Exercise Training Improves Renal Injury in Spontaneously Hypertensive Rats by Increasing Renalase Expression in Medulla - Luo, Minghao; Cao, Shuyuan; Lv, Dingyi; He, Longlin; He, Zhou; Li, Lingang; Li, Yongjian; Luo, Suxin; Chang, Qing (Frontiers in cardiovascular medicine, 2022)
We aimed to examine the effects of aerobic exercise training on renal function in spontaneously hypertensive rats (SHR) and elucidate their possible mechanisms. Adult male SHR and age-matched Wistar-Kyoto rats (WKY) were divided into four groups: WKY sedentary group, SHR sedentary group, low-intensity training group, and medium-intensity training group. Using molecular and biochemical approaches, we investigated the effects of 14-week training on renalase (RNLS) protein levels, renal function, and apoptosis and oxidative stress modulators in kidney tissues. In vitro , angiotensin II (Ang II)-induced human kidney proximal epithelial cells (HK-2) were treated with RNLS, and changes in apoptosis and oxidative stress levels were observed. Our results show that moderate training improved renal function decline in SHR. In addition, aerobic exercise therapy significantly increased levels of RNLS in the renal medulla of SHR. We observed in vitro that RNLS significantly inhibited the increase of Ang II-inducedapoptosis and oxidative stress levels in HK-2. In conclusion, aerobic exercise training effectively improved renal function in SHR by promoting RNLS expression in the renal medulla. These results explain the possible mechanism in which exercise improves renal injury in hypertensive patients and suggest RNLS as a novel therapy for kidney injury patients.